Analysis of Optimal Capital Structure in the Pharmaceutical Industry Companies Listed on the Indonesia Stock Exchange - Wulan Hamida; Ine Mayasari; Banter Laksana; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Capital structure policy is used to help companies determine the optimal composition of capital between debt and equity. This study aims to determine the optimal capital structure of companies in the pharmaceutical industry listed on the Indonesia Stock Exchange for the 2015-2019 period. The data used is secondary data obtained from the financial statements of PT Indofarma Tbk, PT Herbal and Pharmaceutical Industries sido Appear Tbk, PT Kimia Farma Tbk, and PT Merk Tbk which are processed using the method of calculating the cost of capital and comparing returns. On Equity (ROE) with a weighted average cost of capital (Average Weight Cost of Capital). The results showed that PT Indofarmas Tbk had an optimal structure in 2015 and 2019. PT Industri Jamu and Pharmacy Sido Appear Tbk had an optimal capital structure from 2015 to 2017, and PT Kimia Farma Tbk and PT Merk Tbk had an optimal capital structure from 2015. 2015 to 2019. These results can be seen from the ROE generated by the company, which is greater than the WACC in each period.